PRODUKSI BIBIT KENTANG (Solanum tuberosum L.) G1 DARI STEK BATANG - Wina Andriani Lestari, Putu; Ria Defiani, Made; Astarini, Ida Ayu (SIMBIOSIS, 2014)
This research was conducted to find out the best media and auxin for planting potato cutting to produce G1 seed potato. Research was done at a shade house of Kebun Bibit Hortikultura Kembang Merta, Candi Kuning Village, Baturiti, Tabanan Regency, Bali. Were planted at the screen house for sprouting. Four weeks old of shoots were used as cutting. Each cutting measured 10 cm. Stem cutting of G0 seed potatoes was dipped in 2 different auxin types (Rootone F and auxin paste) and planted in 2 different media (manure and charred rice husk). Results shows that the best combination between media and auxin for stem cutting growth was charred rice husk and Rootone F, in which 82.29% growth was recorded. Combination between charred rice husk and Rootone F produced 12 more seed potatoes per plant, compared to other treatment combination. In term of seed potato size, the highest number produced (80%) was size SS (<20 gram) , followed by size S (21-30 gram) which is 66%, size M (31-60 gram) which is 8% and size L (>60%) of 2%. Keyword : Potato (Solanum tuberosum L.), stem cuttings, seed production.